Checklists of methodological issues for review authors to consider when including non‐randomized studies in systematic reviews. (22nd March 2013) - Wells, George A; Shea, Beverley; Higgins, Julian PT; Sterne, Jonathan; Tugwell, Peter; Reeves, Barnaby C; Reeves, Barnaby C.; Wells, George A.
<x xml:space="preserve">Abstract</x> Background There is increasing interest from review authors about including non‐randomized studies (NRS) in their systematic reviews of health care interventions. This series from the Ottawa Non‐Randomized Studies Workshop consists of six papers identifying methodological issues when doing this. Aim To format the guidance from the preceding papers on study design and bias, confounding and meta‐analysis, selective reporting, and applicability/directness into checklists of issues for review authors to consider when including NRS in a systematic review. Checklists Checklists were devised providing frameworks to describe/assess: (1) study designs based on study design features; (2) risk of residual confounding and when to consider meta‐analysing data from NRS; (3) risk of selective reporting based on the Cochrane framework for detecting selective outcome reporting in trials but extended to selective reporting of analyses; and (4) directness of evidence contributed by a study to aid integration of NRS findings into summary of findings tables. Summary The checklists described will allow review groups to operationalize the inclusion of NRS in systematic reviews in a more consistent way. The next major step is extending the existing Cochrane Risk of Bias tool so that it can assess the risk of bias to NRS included in a review. Copyright © 2013 John Wiley & Sons, Ltd.